Increasing Neonatal Mortality among Palestine Refugees in the Gaza Strip - van den Berg, Maartje M. (PLoS One, 2015)
BACKGROUND: The United Nations Relief and Works Agency for Palestine refugees in the Near East (UNRWA) has periodically estimated infant mortality rates among Palestine refugees in Gaza. These surveys have recorded a decline from 127 per 1000 live births in 1960 to 20.2 in 2008. METHODS: We used the same preceding-birth technique as in previous surveys. All multiparous mothers who came to the 22 UNRWA health centres to register their last-born child for immunization were asked if their preceding child was alive or dead. We based our target sample size on the infant mortality rate in 2008 and included 3128 mothers from August until October 2013. We used multiple logistic regression analyses to identify predictors of infant mortality. FINDINGS: Infant mortality in 2013 was 22.4 per 1000 live births compared with 20.2 in 2008 (p = 0.61), and this change reflected a statistically significant increase in neonatal mortality (from 12.0 to 20.3 per 1000 live births, p = 0.01). The main causes of the 65 infant deaths were preterm birth (n = 25, 39%), congenital anomalies (n = 19, 29%), and infections (n = 12, 19%). Risk factors for infant death were preterm birth (OR 9.88, 3.98–24.85), consanguinity (2.41, 1.35–4.30) and high-risk pregnancies (3.09, 1.46–6.53). CONCLUSION: For the first time in five decades, mortality rates have increased among Palestine refugee newborns in Gaza. The possible causes of this trend may include inadequate neonatal care. We will estimate infant and neonatal mortality rates again in 2015 to see if this trend continues and, if so, to assess how it can be reversed.